Ceramic Filters Coated with Green Ag-Nanoparticles for Drinking Water Treatment in Rural Households of Nigeria - Olukemi Aromolaran; Timothy O Ogunbode (SAGE Publishing, 2024)
A ceramic water filter (CWF) coated with plant-based nanoparticles was used as household water purifier in a rural community. Silver nanoparticles (AgNPs) were produced from the stem bark of Bridelia ferruginea plant, and their efficacy to enhance the physical, chemical, and microbial quality of raw stream water sample was determined using analytical probes and pour-plate techniques, respectively. The pH of the filtered water sample ranged 7.6 to 8.1, which is within the WHO permissible limit for drinking water, and the electrical conductivity values were also reduced from 110 to 70 µS/cm. The CWF coated with AgNPs (CWF-AgNPs) removed Klebsiella pnuemoniae, Pseudomonas aeruginosa, Staphylococcus aureus , and Entamoeba histolytica from the stream water sample. The highest percentage of coliform reduction in the CWF and CWF-AgNPs were 93.18% and 99.64%, respectively. The raw data showed that the CWF-NPs enhanced the quality of the stream water. The surface and internal structure of the CWF-AgNPs can be modified by varying the concentration of the composite materials, so as to determine the most effective combination. The improved CWF-AgNPs will enhance achieving United Nations Sustainable Development Goal #6, which focuses on clean water and sanitation.